Asthma improvement in patients treated with dupilumab for severe atopic dermatitis - Dubini, Marco; Benzecry, Valentina; Rivolta, Federica; Sangalli, Andrea; Marzano, Angelo Valerio; Pravettoni, Valerio; Tavecchio, Simona; Ferrucci, Silvia Mariel (Frontiers in Allergy, 2023)
Introduction Atopic dermatitis (AD) is considered a systemic type 2 immune driven disease, and it is associated to many atopic comorbidities including asthma. The aim of our study was to prospectively evaluate the respiratory outcomes in patients with persistent allergic asthma treated with dupilumab due to severe AD (sAD). Methods We enrolled eligible patients with sAD for dupilumab treatment from September 2018 to December 2020. We then selected the subgroup of patients sensitized to perennial allergens. Dupilumab's efficacy and safety on AD and comorbid asthma were assessed at baseline, one month, four months, and then every 4 months up to one year. Results A total of 437 patients with sAD were enrolled for dupilumab treatment due to sAD, and 273 reached 48 weeks of therapy. Respiratory outcomes were evaluated in the 85 asthmatic patients with positivity only to perennial allergens. Our patients showed statistically and clinically significant improvement in asthma control (Asthma Control Test and Asthma Control Questionnaire) and airway obstruction parameters (FEV1), in addition to the expected AD-related skin outcomes. Specifically, a significant improvement was achieved at the fourth month of dupilumab therapy, and this trend was maintained up to twelve months, regardless of asthma severity. Conclusions Our results showed the overall improvement of the clinical picture that dupilumab offers for patients with severe AD and persistent allergic asthma of any severity, highlighting the importance of a global multidisciplinary approach of type 2 driven disease.